Role of the I16-D194 ionic interaction in the trypsin fold - Stojanovski, Bosko M. (Sci Rep, 2019)
Activity in trypsin-like proteases is the result of proteolytic cleavage at R15 followed by an ionic interaction that ensues between the new N terminus of I16 and the side chain of the highly conserved D194. This mechanism of activation, first proposed by Huber and Bode, organizes the oxyanion hole and primary specificity pocket for substrate binding and catalysis. Using the clotting protease thrombin as a relevant model, we unravel contributions of the I16-D194 ionic interaction to Na(+) binding, stability of the transition state and the allosteric E*-E equilibrium of the trypsin fold. The I16T mutation abolishes the I16-D194 interaction and compromises the architecture of the oxyanion hole. The D194A mutation also abrogates the I16-D194 interaction but, surprisingly, has no effect on the architecture of the oxyanion hole that remains intact through a new H-bond established between G43 and G193. In both mutants, loss of the I16-D194 ionic interaction compromises Na(+) binding, reduces stability of the transition state, collapses the 215–217 segment into the primary specific pocket and abrogates the allosteric E*-E equilibrium in favor of a rigid conformation that binds ligand at the active site according to a simple lock-and-key mechanism. These findings refine the structural role of the I16-D194 ionic interaction in the Huber-Bode mechanism of activation and reveal a functional linkage with the allosteric properties of the trypsin fold like Na(+) binding and the E*-E equilibrium.